AFLP Approach Reveals Variability in Phragmites australis: Implications for Its Die-Back and Evidence for Genotoxic Effects - Coppi, Andrea; Lastrucci, Lorenzo; Cappelletti, David; Cerri, Martina; Ferranti, Francesco; Ferri, Valentina; Foggi, Bruno; Gigante, Daniela; Venanzoni, Roberto; Viciani, Daniele; Selvaggi, Roberta; Reale, Lara (Frontiers in Plant Science, 2018)
Phragmites australis is a subcosmopolitan species typical of wetlands being studied in Europe for its disappearance from natural stands, a phenomenon called reed die-back syndrome (RDBS). Although it is conjectured that low genetic variability contributes to RDBS, this aspect remains neglected to this day. Using a molecular fingerprinting approach and a sequence analysis of the trnT-trnL/rbcL-psaI regions of cpDNA, this study aimed to compare the genetic structure of stable vs. RDBS-affected P. australis stands from five wetlands of central Italy. Beforehand, in order to characterize the health condition of reed populations, the occurrence of the main macromorphological descriptors for RDBS was considered on 40 reed stands. Soil samples were also collected to examine the total content of heavy metals. The current study analyzed cpDNA in 19 samples and AFLP profiles in 381 samples to investigate the genetic structure of Phragmites populations. Based on the multinomial-Dirichlet model, an analysis of candidate loci under selective pressure was also performed. The relationships among AFLP data, RDBS descriptors and chemicals were evaluated with the use of Linear Mixed Models. The analysis of the cpDNA shows the occurrence of the haplotypes M (the most widespread), and K here recorded for the first time in Italy. Three new haplotypes were also described. The DNA fingerprinting analysis has produced a total of 322 loci (98% polymorphic) and shows the medium-to-high amount of genetic diversity. The significant genetic differentiation among wetlands (Fst=0.337) suggests either low gene flow or small effective population size. Moreover, the low amount of outlier loci (only 5; l.5% of the total), seems to indicate the scarce occurrence of selective pressure upon the reed’s genome. Genetic diversity increased in relationship to the decrease in diameter and of flowering buds of the reed, two of the trends associated with the dieback. The current study rejects the hypothesis that genetic diversity massively contributed to RDBS. Moreover, significant relationships between genetic diversity and the total concentration of some heavy metals (Cr, Cu and Zn) were highlighted, indicating possible genotoxic effects on P. australis. The current study represents a fact-finding background useful for the conservation of common reed.